2018
DOI: 10.3390/sports6040103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass Index on Acute Cardiometabolic Responses to Graded Exercise Testing in Children: A Narrative Review

Abstract: Although the beneficial role of exercise for health is widely recognized, it is not clear to what extent the acute physiological responses (e.g., heart rate (HR) and oxygen uptake (VO2)) to a graded exercise test are influenced by nutritional status (i.e., overweight vs. normal-weight). Therefore, the main objectives of the present narrative review were to examine the effect of nutritional status on acute HR, and VO2 responses of children to exercise testing. For this purpose, we examined existing literature u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
(103 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, our results are in concordance with previous research on children, which has shown that the HR peak is independent of sex, age, fitness level, and BMI [52,56,57]. Finally, contrary to one study [58], which observed a lower HR Peak between overweight and obese children (aged 6-18 years), this work has been unable to find this relationship.…”
Section: Cardiac Autonomic Function During Maximal Exercisesupporting
confidence: 85%
“…On the other hand, our results are in concordance with previous research on children, which has shown that the HR peak is independent of sex, age, fitness level, and BMI [52,56,57]. Finally, contrary to one study [58], which observed a lower HR Peak between overweight and obese children (aged 6-18 years), this work has been unable to find this relationship.…”
Section: Cardiac Autonomic Function During Maximal Exercisesupporting
confidence: 85%
“…These are important considerations when discussing our findings because the cardiometabolic responses to INT are dependent upon various factors including the intensity of muscle actions, type of muscle actions, the amount of muscle mass used, rest intervals and body position [ 14 , 15 , 40 ]. In addition, age, fitness level and body mass index can influence the acute cardiometabolic responses to exercise and the kinetics of recovery after exercise [ 25 , 34 , 41 ]. Children appear to be less susceptible to neuromuscular fatigue than adults following resistance training [ 42 ] and the post-exercise decline in VO 2 seems to be faster in children with a higher peak VO 2 than those with a lower peak VO 2 [ 34 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from different countries and races have shown that the physical fitness of young people correlates negatively with increasing body fat mass (10,23,24). A higher body mass index (BMI) and increased percentage of fat mass had been proved to be negatively related with the CRF level in children and adolescents with normal weight or overweight status (7,25,26). Our team used CPET to measure the peakVO 2 directly and found that excessive body adiposity, regardless of BMI or fat mass index (FMI), negatively affected the CRF of schoolchildren aged 10-18 years (1).…”
Section: Introductionmentioning
confidence: 99%